γ-Tubulin has a conserved intrinsic property of self-polymerization into double stranded filaments and fibrillar networks - Chumová, Jana; Trögelová, Lucie; Kourová, Hana; Volc, Jindřich; Sulimenko, Vadym; Halada, Petr; Kučera, Ondřej; Benada, Oldřich; Kuchařová, Anna; Klebanovych, Anastasiya; Dráber, Pavel; Daniel, Geoffrey; et al. (Biochimica et biophysica acta. Molecular cell research, 2018)
γ-Tubulin is essential for microtubule nucleation and also plays less understood roles in nuclear and cell-cycle-related functions. High abundancy of γ-tubulin in acentrosomal Arabidopsis cells facilitated purification and biochemical characterization of large molecular species of γ-tubulin. TEM, fluorescence, and atomic force microscopy of purified high molecular γ-tubulin forms revealed the presence of linear filaments with a double protofilament substructure, filament bundles and aggregates. Filament formation from highly purified γ-tubulin free of γ-tubulin complex proteins (GCPs) was demonstrated for both plant and human γ-tubulin. Moreover, γ-tubulin associated with porcine brain microtubules formed oligomers. Experimental evidence on the intrinsic ability of γ-tubulin to oligomerize/polymerize was supported by conservation of α- and β-tubulin interfaces for longitudinal and lateral interactions for γ-tubulins. STED (stimulated emission depletion) microscopy of Arabidopsis cells revealed fine, short γ-tubulin fibrillar structures enriched on mitotic microtubular arrays that accumulated at polar regions of acentrosomal spindles and the outer nuclear envelope before mitosis, and were also present in nuclei. Fine fibrillar structures of γ-tubulin representing assemblies of higher order were localized in cell-cycle-dependent manner at sites of dispersed γ-tubulin location in acentrosomal plant cells as well as at sites of local γ-tubulin enrichment after drug treatment. Our findings that γ-tubulin preserves the capability of prokaryotic tubulins to self-organize into filaments assembling by lateral interaction into bundles/clusters help understanding of the relationship between structure and multiple cellular functions of this protein species and suggest that besides microtubule nucleation and organization, γ-tubulin may also have scaffolding or sequestration functions.
Keywords: Microtubule-Associated Proteins; proteinové agregáty; mikrofilamenta; GCP-free γ-tubulin; Protein Aggregates; polymerizace; Arabidopsis; Actin Cytoskeleton; Mitotic spindle; Mitosis; Cytoskeleton; proteiny asociované s mikrotubuly; Microtubules; Filament self-assembly; mikrotubuly; Polymerization; cytoskelet; mitóza; tubulin; γ-Tubulin; Nucleus; Tubulin